Analysis of fruit and oil quantity and quality distribution in high-density olive trees in order to improve the mechanical harvesting process - Castillo-Ruiz, Francisco J.; Jiménez-Jiménez, Francisco; Blanco-Roldán, Gregorio L.; Sola-Guirado, Rafael R.; Agüera-Vega, Juan; Castro-Garcia, Sergio (Spanish Journal of Agricultural Research, 2015)
Olive fruit production and oil quality distribution with respect to canopy distribution are important criteria for selection and improvement of mechanical harvesting methods. Tests were performed in a high-density olive orchard (Olea europea L., cv. Arbequina) in southern Spain. Fruit distribution, fruit properties and oil parameters were measured by taken separate samples for each canopy location and tree. Results showed a high percentage of fruits and oil located in the middle-outer and upper canopy, representing more than 60% of total production. The position of these fruits along with their higher weight per fruit, maturity index and polyphenol content make them the target for all mechanical harvesting systems. The fruits from the lower canopy represented close to 30% of fruit and oil production, however, the mechanical harvesting of these fruits is inefficient for mechanical harvesting systems. Whether these fruits cannot be properly harvested, enhance tree training to raise their position is recommended. Fruits located inside the canopy are not a target location for mechanical harvesting systems as they were a small percentage of the total fruit (<10%). Significant differences were found for polyphenol content with respect to canopy height, although this was not the case with acidity. In addition, the ripening index did not influence polyphenol content and acidity values within the canopy. Fruit production, properties and oil quality varied depending on fruit canopy position. Thus harvesting systems may be targeted at maximize harvesting efficiency including an adequate tree training system adapted to the harvesting system.